Pengaruh Efikasi Diri Terhadap Prokrastinasi Akademik Mahasiswa Bekerja di Fakultas Psikologi Universitas Buana Perjuangan Karawang - Fattah, Nur Aziizatul; Sadijah, Nur Ainy; Minarsih, Yulyanti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Education is an important component in human life. Formal and informal education are two sociological models of the education system that help in controlling the learning process, especially in higher education. Currently, the surrounding environment which requires a person to study while working can influence the development of academic procrastination which has an impact on psychological elements such as self-efficacy. The aim of this research is to determine the influence between academic procrastination and self-efficacy in psychology study program students at Buana Perjuangan University, Karawang. The methodology used is quantitative, while the sampling technique uses non-probability sampling with a quota sampling technique. Using a 5% error rate in the Isaac Michael methodology, a total of 235 individuals were obtained. The results of hypothesis testing show that there is an influence between academic procrastination and self-efficacy of 10%.